Status is a divine art (Texas Journal of Philology, Culture and History, 2022)
The art of national status, which is an integral part of the cultural heritage of our people, occupies a particularly important place in our spiritual life with its ancient history, deep philosophical roots, unique artistic style and rich creative traditions.